Rembrandt's Ocular Pathologies. Issue 4 (July 2016) - Wiser, Itay; Parnass, Adam J.; Rachmiel, Ronny; Westreich, Melvyn; Friedman, Tali
Abstract : Purpose: This article aims to medically and artistically analyze various ophthalmological ailments documented in self-portraits of Rembrandt to determine if those ailments were medical conditions or stylistic and age-related changes. Methods: A systematic literature review using Pub Med and Google Scholar found 232 results from a search of "Rembrandt" and more than 5, 000 results for "Rembrandt Aging." After extensive review of the literature, the authors found 17 relevant sources. These sources were then supplemented with historical books on Rembrandt and the aging processes of artists. Analytical observations with proportional measurements of anthropometrical landmarks (from self-portraits of Rembrandt at various ages) were studied, measured, analyzed, and compared using a standardized technique via MB ruler graphic software to assess age- or medically related changes. Results: The ophthalmological problems cited in the literature related to Rembrandt's periorbital structures were found by the authors to be false. Signs of inappropriate aging and ailments, such as hyperthyroidism were deemed inaccurate by the authors based on absence of classical disease progression. Ophthalmological problems cited in the literature on Rembrandt's visual acuity were found to be stylistic changes or considered normal aging. Finally, the authors found that ophthalmological problems relating to Rembrandt's eye and orbital adnexa are unfitting because these problems were not seen in subsequent paintings. Conclusions: The authors believe that all the physical changes seen in Rembrandt's portraits represent natural age-related or stylistic changes, and do not represent signs or symptoms of diseases in the master. Abstract : Rembrandt's potential ophthalmological problems reflected from his artwork, regarding periorbital structures, visual acuity, and eye and orbital adnexa were found to be either age related or stylistic changes and not indicative of disease processes.